A statistical study of the high prolactin hormone and its relationship to male and female infertility in the Najaf district - Habeeb Obaid , nada (Pure Sciences International Journal of Kerbala, 2024)
Aim of study: Toward studying the effects of prolactin, LH, and FSH hormones on male infertility in Najaf district. Methods: One hundred and sixty-four healthy, fertile men and women served as the control group, whereas 184 infertile men and women from enrollments came from the Infertility Center, Al-Sadr Medical City, and Al. Najaf City. They are in the age range of 20 to 70. Results: According to the findings, the LH mean ± st the control group's IU/L was 4.37±0.35. There were notable variations in the F.S.H. value (8.74±1.43IU/L). andard deviation was 16.25±4.6 IU/L, whereas the value for the control group was 4.37±0.35 IU/L. Significant differences were seen in the F.S.H. value (8.74±1.43IU/L) between the infertile patient group and the control group (men and women) (5.33±0.44IU/L)., Prolactin levels in the patients were 53.12±5.68 (IU/L) and 19.25±1.23 (IU/L) in the control group, respectively. There was no statistically significant difference between the control group and the cases study. The same can be said about control group or the cases study.On the other hand, levels of prolactin and F.S.H. fall modestly with age, whereas levels of L.H. increase. Conclusion: The findings of this study indicate that in order to classify infertility patients into male and female groups and estimate a comprehensive case and control, research should be carried out for both male and female infertility due to the hormonal imbalance of L.H., F.S.H., and prolactin.